Development of staffing, workload and infrastructure in member departments of the European Organisation for Research and Treatment of Cancer (EORTC) radiation oncology group. (February 2021) - Willmann, Jonas; Poortmans, Philip; Monti, Angelo Fillipo; Grant, Warren; Clementel, Enrico; Corning, Coreen; Reynaert, Nick; Hurkmans, Coen W.; Andratschke, Nicolaus
Highlights: The number of patients treated annually per radiation oncology department increases over time. Case-related workload decreases for radiation oncologists and physicists. For radiation therapists and treatment units, case-related workload increases. Complex and more accurate radiation therapy techniques become more widely available. These are time-demanding for preparation and per session, yet involve less fractions. Abstract: Purpose: The EORTC Radiation Oncology Group uses a Facility Questionnaire (FQ) to collect information from its member radiation oncology departments. We analysed the FQ database for patient-related workload, staffing levels and infrastructure to determine developments in radiation oncology departments in the clinical trials community. Materials & Methods: We exported the FQ database in August 2019. Departments were included if their FQ was created or updated within the two preceding years. Observations were compared with previous evaluations of the FQ database. Results: In total, 161 departments from 24 mostly European countries were analysed. The average number of patients per department increased by 3.0% to 2, 453 (2013: 2, 381). The annual number of patients decreased by 7.4% to 225 per radiation oncologist (2013: 243) and by 7.9% to 326 per medical physicist (2013: 354). In contrast, the number of patients increased by 23.3% to 106 per radiation therapist (RTT) (2013: 86) and per treatment unit by 3.9 % to 485 (2013: 467). In a pairwise comparison of departments that were available in 2013 and 2019, the number of patients per radiation oncologist ( p = 0.02) and per physicist ( p = 0.0003) decreased significantly. The number of departments that own a dedicated PET-CT scanner more than doubled (2013: 4%; 2019: 9%) and the availability of stereotactic body radiation therapy (SBRT) increased by 31.8% to 85.7% of the departments (2013: 65%). Conclusion: The case-related workload per radiation oncologist and per physicist continues to decrease but increases per RTT and treatment unit. This is likely driven by an increased use of complex techniques, multimodality imaging and the implementation of automation in radiation oncology departments.